Performance Analysis of the National Early Warning Score and Modified Early Warning Score in the Adaptive COVID-19 Treatment Trial Cohort - Christopher J. Colombo, MD, MA, FACP, FCCM; Rhonda E. Colombo, MD, MHS, FACP, FIDSA; Ryan C. Maves, MD, FCCM, FCCP, FIDSA; Angela R. Branche, MD; Stuart H. Cohen, MD; Marie-Carmelle Elie, MD; Sarah L. George, MD; Hannah J. Jang, PhD, RN, CNL, PHN; Andre C. Kalil, MD, MPH; David A. Lindholm, MD, FACP; Richard A. Mularski, MD, MSHS, MCR, ATSF, FCCP, FACP; Justin R. Ortiz, MD, MS, FACP, FCCP; et al. (Critical Care Explorations)
OBJECTIVES:. We sought to validate prognostic scores in coronavirus disease 2019 including National Early Warning Score, Modified Early Warning Score, and age-based modifications, and define their performance characteristics. DESIGN:. We analyzed prospectively collected data from the Adaptive COVID-19 Treatment Trial. National Early Warning Score was collected daily during the trial, Modified Early Warning Score was calculated, and age applied to both scores. We assessed prognostic value for the end points of recovery, mechanical ventilation, and death for score at enrollment, average, and slope of score over the first 48 hours. SETTING:. A multisite international inpatient trial. PATIENTS:. A total of 1,062 adult nonpregnant inpatients with severe coronavirus disease 2019 pneumonia. INTERVENTIONS:. Adaptive COVID-19 Treatment Trial 1 randomized participants to receive remdesivir or placebo. The prognostic value of predictive scores was evaluated in both groups separately to assess for differential performance in the setting of remdesivir treatment. MEASUREMENTS AND MAIN RESULTS:. For mortality, baseline National Early Warning Score and Modified Early Warning Score were weakly to moderately prognostic (c-index, 0.60–0.68), and improved with addition of age (c-index, 0.66–0.74). For recovery, baseline National Early Warning Score and Modified Early Warning Score demonstrated somewhat better prognostic ability (c-index, 0.65–0.69); however, National Early Warning Score+age and Modified Early Warning Score+age further improved performance (c-index, 0.68–0.71). For deterioration, baseline National Early Warning Score and Modified Early Warning Score were weakly to moderately prognostic (c-index, 0.59–0.69) and improved with addition of age (c-index, 0.63–0.70). All prognostic performance improvements due to addition of age were significant (p < 0.05). CONCLUSIONS:. In the Adaptive COVID-19 Treatment Trial 1 cohort, National Early Warning Score and Modified Early Warning Score demonstrated moderate prognostic performance in patients with severe coronavirus disease 2019, with improvement in predictive ability for National Early Warning Score+age and Modified Early Warning Score+age. Area under receiver operating curve for National Early Warning Score and Modified Early Warning Score improved in patients receiving remdesivir versus placebo early in the pandemic for recovery and mortality. Although these scores are simple and readily obtainable in myriad settings, in our data set, they were insufficiently predictive to completely replace clinical judgment in coronavirus disease 2019 and may serve best as an adjunct to triage, disposition, and resourcing decisions.